The Impact of Arts Education on Cognitive Development and Academic Performance - Zining Liu (Journal of Advanced Research in Education, 2023)
This article explores the factors influencing the effectiveness of arts education on cognitive development and academic performance. It discusses the importance of quality instruction, duration and intensity of programs, integration with the curriculum, access and equity, supportive school environments, parental and community involvement, and individual student characteristics. Recommendations for educators, policymakers, and curriculum development are provided, emphasizing the need for clear goals, professional development, collaboration, interdisciplinary integration, diverse assessment methods, resources, community engagement, and research. The article concludes by highlighting the significance of further research to explore the long-term effects of arts education on cognitive development and academic performance.